Covid stories from East Africa and beyond : lived experiences and forward-looking reflections (LANGAA RPCID, 2020)
The coronavirus has rattled humanity, tested resolve and determination, and redefined normalcy. This compelling collection of 29 short stories and essays brings together the lived experiences of covid19 through a diversity of voices from across the African continent. The stories highlight challenges, new opportunities, and ultimately the deep resilience of Africans and their communities. Bringing into conversation the perspectives of laypeople, academics, professionals, domestic workers, youth, and children, the volume is a window into the myriad ways in which people have confronted, adapted to, and sought to tackle the coronavirus and its trail of problems. The experiences of the most vulnerable are specifically explored, and systemic changes and preliminary shifts towards a new global order are addressed. Laughter as a coping mechanism is a thread throughout.